PENERAPAN SISTEM INFORMASI PELAYANAN MASYARAKAT BERBASIS WEB MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Mochammad Donni Kurniawan; Yunianita Rahmawati; Uce Indahyanti (Politeknik Bisnis Indonesia, 2024)
This research is to design a web-based community service system application (SIMPELMASWEB) which aims to help parties related to the Pogar – Bangil sub-district in providing services so that services become more effective and efficient. The research model used is Rapid Application Development (RAD), there are several stages carried out as follows: (1) Planning a Requirement, (2) Application System Design, (3) Process of developing and collecting feedback, (4) Implementation and completion of the product From the results of this research which have been tested, it shows that the SIMPELMASWEB application can be used according to its function so that it makes it easier for related parties to serve the Pogar community efficiently and effectively.